O-GlcNAc, an essential regulator of numerous cellular pathways - Zachara, Natasha (Henry Stewart Talks, 2014)
O-GlcNAc, A Novel Intracellular Glycan, Biosynthesis of O-GlcNAc, Mechanisms by which O-GlcNAc regulates proteins, Cellular pathways and diseases regulated by O-GlcNAc, Epigenetics and transcription, Translation, Cell cycle, Nutritional sensing, Neurodegeneration, Cancer, The cellular stress response